Strategies for Utilizing AI and Data Analytics to Improve the Effectiveness of Public Services in Indonesia: A Local Government Level Approach - Loso Judijanto; Taufiqurokhman Taufiqurokhman; Satya Arisena Hendrawan; Herwanto Herwanto (West Science Business and Management, 2023)
This research investigates the strategies for utilizing artificial intelligence (AI) and data analytics to enhance the effectiveness of public services within Indonesian local governments. A quantitative analysis was conducted, involving a diverse sample of 200 participants, including local government officials, IT professionals, and citizens across various regions. The study employs a structural equation modeling approach, assessing the relationships between the implementation of AI, data analytics, and the effectiveness of public services. The measurement model confirms the reliability and validity of the constructs, while the structural model reveals significant positive paths from both data analytics and AI utilization to public service effectiveness. The findings contribute to the evolving landscape of technological integration in public administration, offering evidence-based insights for policymakers and practitioners.